Leveraging six sigma tools to improve student performance in technical courses at secondary school - Miza Liyana Taha, Sulaiman; Muhammed Nafis, Osman Zahid (Institution of Engineering and Technology, 2022)
The goal of this study is to analyze student performance, improve Reka Bentuk Teknologi (RBT) course for Form 3 students using Six Sigma tools and to identify root causes of performance and make recommendations for improving results at one of the secondary school in Johor. According to an analysis conducted, the subject committee is looking forward to the number of students who will get Grade B and attend the examination for this subject in the final examination increasing by the end of the school session. To improve student performance in the RBT course, this paper employs various quality improvement tools during the Define, Measure, Analyze, Improve, and Control (DMAIC) phases. The study elucidates the causes of students' Mid-term examination results and enables recommendations to be made to improve student performance in RBT course. Six Sigma tools such as the Cause and Effect Diagram (Fishbone Diagram), Pareto Chart, and Quality Function Deployment (QFD) have been successfully adopted as quality tools during the improvement phase to make recommendations for improving student performance in technical courses. This research study also assists the course committee and school administration in learning more about the problems that students face and the improvement plans that they can implement in order to improve students' grades and interest in the course. Therefore, this research study is to improve students' grades and exam attendance, analyze student understanding in each chapter, and solve problems that arise by using the QFD tool.